OPEN EDUCATION AS A PHILOSOPHICALLY METHODOLOGICAL BASIS FOR DISTANCE EDUCATION - Katane, Irēna; Katans, Edgars; Vāvers, Valdis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Over the centuries, humanity's notions and worldview of what education should be have changed constantly in the order it serves both the development goals of society as a whole and the interests and needs of each individual. In the global educational environment, including Latvia, several educational paradigms have emerged and nowadays coexist which often complement each other. Among them, the Open Education paradigm plays an important role, where the main emphasis is on access to education. The aim of the research: to substantiate Open Education as a philosophical-methodological basis for distance education. The results of the research show that the origins of Open Education can be found in the philosophical thought of the Enlightenment era philosophers, as well as representatives of education, culture, and religion. The roots of the Open Education ideas can be traced to the history of distance learning, these ideas developed in close connection with the development of distance education/distance learning theories and their implementation in practice. From the 18th century to the present day, the ideas of Open Education developed and supplemented with new views on the aims, basic dimensions and principles, and functions of education, gaining more larger interpretation of this concept. At the end of the twentieth century, Open Education became the basis for a new educational paradigm in the Postmodernism era not only regarding distance education. Open Education became one of the most important doctrines of Postmodernism in the development of education, according to which the concepts of open education, open educational environment, and open school developed. There are three dimensions of Open Education: space, time, and process. Open Education and distance education have common three basic principles: openness, respect for distance in providing education, and flexibility.